2009
DOI: 10.1080/02688690802610249
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical discectomy: to graft or not to graft?

Abstract: The debate regarding whether to perform an interbody fusion after anterior cervical discectomy (ACD) has been going on for the last 50 years. Several prospective randomized clinical trials have been performed to evaluate the clinical outcome following anterior cervical discectomy with and without interbody fusion. None of these studies show a significant difference between the two techniques in terms of relief of arm pain or neck pain. The operative time, in-hospital stay and time for return to work seem to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…[27] They observed that even in the multiple randomized prospective trials comparing ACF with ACDF, there was “no significant difference” in the relief of arm or neck pain. Differences included for the ADF patients, “…a temporary increase in postoperative axial neck pain”, while the ACDF patients required longer operative times, prolonged lengths of stay, and more time to return to work.…”
Section: Fusion Rates For Non-plated 1-level Anterior Diskectomy Withmentioning
confidence: 99%
“…[27] They observed that even in the multiple randomized prospective trials comparing ACF with ACDF, there was “no significant difference” in the relief of arm or neck pain. Differences included for the ADF patients, “…a temporary increase in postoperative axial neck pain”, while the ACDF patients required longer operative times, prolonged lengths of stay, and more time to return to work.…”
Section: Fusion Rates For Non-plated 1-level Anterior Diskectomy Withmentioning
confidence: 99%
“…Data on the long-term clinical, functional, and radiologic outcomes following these techniques have been reported proposing equally good results in comparison with the [1][2][3][4][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] fusion techniques.…”
Section: S Backgroundmentioning
confidence: 99%
“…On the other hand, the clinical results of ACD are reported to be favorable by numerous studies, which introduce this technique a safe and valuable alternative for the "fusion" [1][2][3][4][11][12][13][14][15][16][17][18][19][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]37 operations with less complication for the patient. However, still the issue of whether to perform fusion or not after anterior cervical discectomy remains controversial, and many comparative prospective clinical studies comparing the outcome of ACD alone with ACDF have failed to prove the superiority of either 1,4,11,12,14,17,18,[21][22][23][24]26,29,34,35 technique. Table 7 shows the variations in the design of the available studies for this narrative review comparing ACD and ACDF and Table 8...…”
Section: Comparison Between Acd and Fusion Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a correlation with a clinical effect has never been established. 17 The most common complications of CAD are hoarseness and dysphagia. A lesion of the recurrent laryngeal nerve can lead to dysfunction.…”
mentioning
confidence: 99%